Ocean salinity measurement using remote sensing data. - Ekechukwu, Boniface; Mansor, Shattri; Mohamed, Mohamed Ibrahim; Emeka, Madu Magnus
Ocean salinity is a very important parameter for ocean fishery industry. The importance of scientific fishery resources development has necessitated this research. Water salinity is often measured to help the fishermen in locating their targets. But measurement of ocean salinity has formally been possible only by using traditional ships' methods. In consequence, this research has developed another way of measuring ocean salinity using satelite data. The research has shown that there is correlation between the watercolor, water salinity and properties like abundance of fish and water turbudity. The work has correlated quantitatively the optical properties of water with relevant biological, biochemical and physical water parameters.